Sensibilidade a antimicrobianos e sorotipos de Streptococcus pneumoniae isolados de portadores e de indivíduos com infecção sistêmica em Fortaleza, Brasil - Laranjeira, Bruno Jaegger (2010)
Streptococcus (S.) pneumoniae is considered the principal causative agent of morbidity and mortality in children younger than five years of age. All pneumococcal diseases are initiated by establishing a S. pneumoniae colonization in nasopharynx, the disease progressing to systemic disease if natural barrier are crossed. During the last decades, the increasing amount of resistant S. pneumoniae strains to beta-lactams and other classes of antimicrobials has modified the treatment of pneumococcal infection. At present, nearly 13 serotypes respond for more than 85% of invasive isolates. The 7-valent polysaccharide-conjugated pneumococcal vaccine has been widely recommended for use in children younger than five years. The aims of this study were to determine the S. pneumoniae carrier in children, the frequence of serotypes from systemic infection patients, the susceptibility profile to antimicrobials in Fortaleza, Brazil. Carrier state isolates were recovered from nasopharyngeal swabs from children attending day-care center facilities, while the isolates from systemic infection fournished by LACEN-CE. Minimal Inhibitory Concentrations (MIC) to penicillin and ceftriaxone were assessed for all isolates, and levofloxacin MIC only from nasopharyngeal isolates. MIC cut-offs were determined according to CLSI standards (2007). Serotyping of systemic isolates was performed by Quellung reaction, while capsular genotyping of carrier isolates was performed by multiplex PCR assay. OF 215 children attending day-care centers, 152 S. pneumoniae isolates were identified (71%). Penicillin MIC showed 71% of resistance, and for ceftriaxone, 21% of resistance. No resistance was found for levofloxacin MIC testing. When compared to a 10-year old similar study in Fortaleza, our results have shown a significant increase of penicillin and ceftriaxone resistance rates. Of 26 isolates tested, only six nasopharyngeal isolates (23%) were positively genotyped by multiplex PCR. The incidence of invasive isolates was 1/100,000 inhab. per year. Of 52 systemic isolates serotyped, 42% were penicillin-resistant, and 13.5% were ceftriaxone-resistant. Systemic serotypes identified were 19F, 3, 6A, 4, 18C and 9V, with a estimated coverage by the 7-valent and 10-v pneumococcal polysaccharide conjugated vaccines of 31.8%.